Terapi Ruqyah Syar’iyyah di Klinik Pusat Bekam Ruqyah Medan (Studi Kasus di Jl. Prof. H.M. Yamin No.305 Sei Kera Hulu Kecamatan Medan Perjuangan) - Dongoran, Roito (UIN Sumatera Utara, 2024)
Medical treatment in Islam, according to the agreement of the scholars, is permissible and even recommended to find a doctor who is an expert to treat internal and external diseases that a person suffers with drugs that are known in medical science. There are still people in society who have an incorrect perception of ruqyah. In general, people know ruqyah as an antidote to jinn disorders or things that are supernatural. It is very rare to find people who do not have an educational background in the medical world but have a passion for concentrating on the world of medicine in the Prophet's way. After conducting research, this research focuses on the Ruqyah method used at the Beqam Ruqyah Medan Center Clinic, namely the Ruqyah Syar'iyyah method, where from the Ruqyah procession there are several methods in its implementation such as the emotional canalization method, Parts Therapy, and counseling. According to the Islamic view of the Ruqyah Syar'iyyah method, it is permissible (mubah), as a treatment medium recommended by the Prophet, it is even said to be the best treatment. This ruqyah method is legally accompanied by the Surahs and Hadiths that have been explained in it. The ruqyah method at Beqam Ruqyah Medan Center tries to look at the symptoms of the patient's disorder not only from one point of view, but from the psychological side of the patient by using counseling methods, emotional canalization, and Parts Therapy. Which aims to find the root of the problem experienced by patients scientifically. Faith is closely related to the soul, high or low faith depends on the health of one's soul. The method used in this research is field research, this study uses descriptive data analysis techniques. Where data sourced from manuscripts, interviews, field notes, documents and so on are then described so as to provide clarity on reality or reality.